PEDAGOGIKALÍQ PROCESSTI NÁTIYJELI BASQARÍWDA OQÍTÍWSHÍNÍŃ ORNÍ HÁM ÁHMIYETI - Tajbenova, S. (SCIENCE and SOCIETY, 2021)
The fact that pedagogical management skills are one of the most important principles of the social education system. It is noted that all conditions have been created in our country for the implementation of this principle. In addition, for the successful development of our society, it must have a high potential, the higher the consciousness, spiritual culture of its members, the more successful the republic, the scientific management of social education, cultural and social services are given.
Keywords: management skills; management; manage; leadership; potential